Observation of nuclear modification of energy-energy correlators inside jets in heavy ion collisions - V. Chekhovsky; A. Hayrapetyan; V. Makarenko; A. Tumasyan; W. Adam; J.W. Andrejkovic; L. Benato; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; P.S. Hussain; et al. (Physics Letters B)
Energy-energy correlators are constructed by averaging the number of charged particle pairs within jets, weighted by the product of their transverse momenta, as a function of the angular separation of the particles within a pair. They are sensitive to a multitude of perturbative and nonperturbative quantum chromodynamics phenomena in high-energy particle collisions. Using lead-lead data recorded with the CMS detector, energy-energy correlators inside high transverse momentum jets are measured in heavy ion collisions for the first time. The data are obtained at a nucleon-nucleon center-of-mass energy of 5.02 TeV and correspond to an integrated luminosity of 1.70nb−1. A similar analysis is done for proton-proton collisions at the same center-of-mass energy to establish a reference. The ratio of lead-lead to proton-proton energy-energy correlators reveals significant jet substructure modifications in the quark-gluon plasma. The results are compared to different models that incorporate either color coherence or medium response effects, where the two effects predict similar substructure modifications.